PENGARUH CITRA MEREK, GAYA HIDUP, DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN IPHONE (Studi Kasus pada Konsumen Renan Store) - Hanifah Luthfiana, (2021)
This research is about iPhone purchase decisions using quantitative descriptive methods performed on the iPhone. iPhone is a line of smartphones designed and marketed by Apple Inc. The iPhone uses Apple's iOS mobile phone operating system known as the "iPhone OS". The purpose of this research is to analyze and prove whether the purchase decision on this iPhone is influenced by the Brand Image, Lifestyle, and Product Quality. The population in this study is the Renan Store consumers who use the iPhone. Samples taken as many as 75 respondents with random sampling method. By distributing questionnaires to Renan Store consumers who use iPhones during the data collection process. The data analysis technique used is descriptive analysis and inferential analysis with the analysis tool used is PLS (Partial Least Square). The results showed that the brand image variable has a correlation value of 0.639, the correlation value of Lifestyle -0.243 and the correlation value of product quality is 0.353 which means it has a partial and significant effect on purchasing decisions. From the analysis of the coefficient of determination, it can be explained that the brand image, lifestyle, and product quality affect the iPhone purchase decision for Renan Store consumers by 68.1%, while the remaining 31.9% is influenced by other variables outside of this research model.